2022
DOI: 10.3389/fneur.2022.840892
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review - Combining Neuroprotection With Reperfusion in Acute Ischemic Stroke

Abstract: BackgroundClinical trials of neuroprotection in acute ischemic stroke (AIS) have provided disappointing results. Reperfusion may be a necessary condition for positive effects of neuroprotective treatments. This systematic review provides an overview of efficacy of neuroprotective agents in combination with reperfusion therapy in AIS.MethodsA literature search was performed on the following databases, namely PubMed, Embase, Web of Science, Cochrane Library, Emcare. All databases were searched up to September 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…First, there is a lack of clinical trials on cytoprotective agents in combination with reperfusion therapy in AIS. Preliminary results from different studies indicate a high potential for some neuroprotective treatments in addition to reperfusion; however more data is needed ( 75 ). Second, Cerebrolysin has been regarded as an ideal agent for functional recovery after AIS because of its multiple attributes including cytoprotective properties and neurotrophic activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a lack of clinical trials on cytoprotective agents in combination with reperfusion therapy in AIS. Preliminary results from different studies indicate a high potential for some neuroprotective treatments in addition to reperfusion; however more data is needed ( 75 ). Second, Cerebrolysin has been regarded as an ideal agent for functional recovery after AIS because of its multiple attributes including cytoprotective properties and neurotrophic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies show the importance of neuroprotection therapy together with reperfusion modalities. In this context, a recent systematic review showed that 5 out of 15 clinical trials indicated that patients treated with neuroprotection and reperfusion therapy had good clinical outcomes ( 65 ). These findings indicate the promising clinical future of using neuroprotection therapy for patients with AIS.…”
Section: Methodsmentioning
confidence: 99%
“…Novel pharmaceutical and non-pharmaceutical methods for recovering cerebral perfusion and neuroprotection are highly sought. Although some drugs were promising in preclinical models for improving cerebral perfusion and rescuing ischemic areas, their use has not translated to clinical settings due to the failure to include stroke models with significant comorbidities and a lack of testing in older animal models [ 9 , 15 , 16 ]. Still, several clinical trials have yielded positive results and indicated beneficial effects in stroke patients, such as the use of human urinary kallidinogenase (HUK) (NCT03431909 Phase IV China), edaravone (NCT02430350 Phase III China/Japan), and nerinetide (NA-1) (NCT02930018 Phase III Canada and USA) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%